Supply-Side School Improvement and the Learning Achievement of the Poorest Children in Indigenous and Rural Schools : The Case of PARE - Paqueo, Vicente; Lopez-Acevedo, Gladys (World Bank, Washington, DC, 2014)
In the past, research findings indicated that most of the differences in student learning were due to socioeconomic factors, and that, therefore, the effect of direct educational interventions to reduce learning inequality was very limited. However, the authors show that learning achievement could increase through appropriately designed, and reasonably well-implemented interventions. An examination of Mexico's PARE program reveals that an increase in learning achievement could be possible for rural, and indigenous schools. The authors' overall conclusion is that supply-side interventions can have substantial effects on the learning achievement of children in indigenous, and rural schools in poor areas. But greater attention needs to be paid to the poorest of the disadvantaged children. This positive conclusion, however, should be tempered by results of the urban sample, confirming earlier findings of the negative relationship between PARE, and student learning growth.